Prey composition in the Persian leopard distribution range in Iran. - Sanei, Arezoo; Hussin, Mohamed Zakaria; Hermidas, Shirin (2011)
A study was conducted in 67 protected areas throughout the Islamic Republic of Iran from 2002 to 2006 to investigate diversity and composition of the Persian leopard potential prey species over its distribution range in the country. The study was performed concurrently with leopard distribution studies using direct observations, rapid survey techniques and collection of secondary data. Nine species, namely: wild goat (Capra aegagrus), wild sheep (Ovis orientalis), Persian gazelle (Gazella subgutturosa), chinkara or jebeer gazelle (Gazellabennettii), wild pig (Sus scrofa), roe deer (Capreolus capreolus), red deer (Cervus elaphus), Indian crested porcupine (Hystrix indica) and Persian wild ass (Equus onager) were studied as the leopard potential prey species. Although attack of leopard on the Persian wild ass is recorded, we excluded the species from the results due to its limited distribution range. Results indicated that wild goat and wild sheep followed by wild pig and Indian crested porcupine are the most widely distributed potential prey species in the leopard distribution range in Iran. Moreover, leopard presence is highly correlated with presence of the wild goat and wild sheep. Nevertheless, opportunistic predation on smaller species such as hare and rodents is likely as leopard has a diverse diet. Eleven sites are proposed as the most considerable sites with regard to the diversity of prey communities. It is suggested that a leopard national conservation plan is essential to protect the leopard particularly as an umbrella species in itscurrent proposed distribution range. However, the priorities in allocation of resources could be given to the sites have been identified through this study to have the most diverse prey communities (i.e. Golestan, Jahan Nama, Parvar, Touran, Khosh Yeilagh, Sorkheh Hesar,Kavir, Sarigol and Salook).